Data-aided synchronization algorithm dispensing with searching procedures for UWB communications - Ren, ZhiYuan; Jiang, Ting; Zhong, Yi; Zhao, ChengLin (Science China. Information sciences, 2012)
Rapid and accurate synchronization constitutes a major challenge in deploying Ultra-Wideband impulse radio （UWB-IR） for indoor wireless communications. This paper develops a data-aided （DA） synchro- nization algorithm dispensing with searching procedures for UWB-IR communications. By adopting a stream of alternating orthogonal pulses, frame-level synchronization can be achieved without channel information. With- out utilizing any searching procedure, the timing offset estimator is obtained in a closed form. Because exhaustive search can be avoided, both computational complexity and synchronization time are reduced. Simulations and comparisons are provided to illustrate the advantages of our design over the alternatives.